UPAYA WORLD FOOD PROGRAMME DALAM MENCAPAI KEAMANAN PANGAN MELALUI INDONESIA COUNTRY PROGRAMME - Zaidan, Muhammad Raihan; Pakpahan, Saiman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Food security is the physical, social, and economic access to sufficient, safe, and nutritious food. Indonesia faced challenges in achieving food security, although there had been progress. Collaborative programs with the World Food Programme (WFP), such as Indonesia Country Programme 1 (2012-2015) and Indonesia Country Programme II (2016-2020), aimed to improve nutrition, disaster preparedness, and food security analysis, in line with the RPJMN. In this study, the author employed an approach the Theory of International Organization and the group-level analysis to analyze and understand events based on existing data. The author utilized qualitative research methods, secondary data collection techniques obtained through a literature review sourced from various publications. WFP had a significant role in achieving food security through the Indonesia Country Programme. As an international organization, WFP successfully fulfilled three roles according to Clive Archer. This fulfillment was observed based on the achievements of the WFP program, namely the Indonesia Country Programme 2016-2020, with the analysis of the four pillars of FAO food security. Keywords : Food Security, World Food Programme, Indonesia Country Programme, International Organization